A case report of a patient with inoperable primary diffuse leptomeningeal melanomatosis treated with whole-brain radiotherapy and pembrolizumab. Issue 3 (21st January 2022) - Palacka, Patrik; Slopovsky, Jan; Makovnik, Marek; Kajo, Karol; Obertova, Jana; Mego, Michal
Abstract: Rationale: Primary diffuse leptomeningeal melanomatosis (PDLM) is a rare disease that affects melanocytes in the leptomeninges. There is very limited data on the efficacy of immunotherapy in this setting. Patient concerns: A patient (23 years old) was diagnosed with PDLM. Histologically, atypical melanocytic cells were also observed. Diagnosis: Immunohistochemistry showed positivity for S100 protein, NKiC3, and vimentin, and negativity for Melan-A and HMB-45, with a proliferation index of 30%. Extracranial disease was excluded using dermatological and other examinations, including positron emission tomography/computed tomography with 18 F-fluorodeoxyglucose. Interventions: The patient was treated with whole-brain radiotherapy (10 fractions to a total dose of 30 Gy) concomitantly with pembrolizumab and then continued with immunotherapy until disease progression with a maximum effect of partial remission on magnetic resonance imaging scans. Outcomes: Progression-free survival was 6.0 months and overall survival 6.5 months. Lessons: This is one of the few case reports of an adult patient with this rare malignancy being treated with a programmed death-1 inhibitor with partial response. Immunotherapy in metastatic PDLM may be a reasonable therapeutic option.